Analysis of device parameters of Al/In2O3/p-Si Schottky diode - Gupta, R. K.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
Thin film of indium oxide (In2O3) is deposited on p-silicon substrate using sol-gel spin technique. The sal-gel spin deposited film is very smooth with grain size and root mean square surface roughness of similar to 40 nm and similar to 7.9 nm, respectively. The device parameters of Al/In2O3/p-Si Schottky diode were investigated using direct current current-voltage (I-V) and impedance spectroscopy. The ideality factor and barrier height of the diode were determined to be 1.07 +/- 0.03 and 0.72 +/- 0.02 eV, respectively. At higher voltages, the charge transport mechanism of the diode is controlled by a trap-charge limited conduction mechanism (TCLC). The series resistance profile of the diode was extracted to show the presence of the interface states changing with frequency. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Indium oxide; Schottky diode; Sol-gel; Current-voltage; Capacitance-voltage